Rab11 and actin cytoskeleton participate in Giardia lamblia encystation, guiding the specific vesicles to the cyst wall. - Araceli Castillo-Romero; Gloria Leon-Avila; Ching C Wang; Armando Perez Rangel; Minerva Camacho Nuez; Carlos Garcia Tovar; Jorge Tonatiuh Ayala-Sumuano; Juan Pedro Luna-Arias; Jose Manuel Hernandez (Public Library of Science (PLoS), 2010)
Giardia passes through two stages during its life cycle, the trophozoite and the cyst. Cyst formation involves the synthesis of cyst wall proteins (CWPs) and the transport of CWPs into encystation-specific vesicles (ESVs). Active vesicular trafficking is essential for encystation, but the molecular machinery driving vesicular trafficking remains unknown. The Rab proteins are involved in the targeting of vesicles to several intracellular compartments through their association with cytoskeletal motor proteins.In this study, we found a relationship between Rab11 and the actin cytoskeleton in CWP1 transport. Confocal microscopy showed Rab11 was distributed throughout the entire trophozoite, while in cysts it was translocated to the periphery of the cell, where it colocalized with ESVs and microfilaments. Encystation was also accompanied by changes in rab11 mRNA expression. To evaluate the role of microfilaments in encystation, the cells were treated with latrunculin A. Scanning electron microscopy showed this treatment resulted in morphological damages to encysted parasites. The intensity of fluorescence-labeled Rab11 and CWP1 in ESVs and cyst walls was reduced, and rab11 and cwp1 mRNA levels were down-regulated. Furthermore, knocking down Rab11 with a hammerhead ribozyme resulted in an up to 80% down-regulation of rab11 mRNA. Although this knockdown did not appear lethal for trophozoites and did not affect cwp1 expression during the encystation, confocal images showed CWP1 was redistributed throughout the cytosol.Our results indicate that Rab11 participates in the early and late encystation stages by regulating CWP1 localization and the actin-mediated transport of ESVs towards the periphery. In addition, alterations in the dynamics of actin affected rab11 and cwp1 expression. Our results provide new information about the molecules involved in Giardia encystation and suggest that Rab11 and actin may be useful as novel pharmacological targets.